Urban planning and the housing market : international perspectives for policy and practice - Gurran, Nicole; Bramley, Glen (Palgrave Macmillan, 2017)
This book re-examines the role of urban policy and planning in relation to the housing market in an era of global uncertainty and change. The relationship between planning and the housing market is a contested problem across research, policy, and practice. Problems with housing supply and affordability in many nations have been linked to planning system constraints, while the global financial crisis has raised new questions about the role of urban planning regulation and processes in responding to housing market trends. With reference to international cases from the United Kingdom, the United States, Ireland, Hong Kong and Australia, the book examines how different systems of urban planning and governance address complex and dynamic housing market trends. It also offers practical guidance on how urban planning can support an efficient supply of appropriate and affordable homes in preferred locations. A detailed study, which explains and decodes the workings of the planning system and housing market, this book will be of particular interest to scholars of human geography and urban planning, as well as housing policy makers and practitioners.- Resumé vydavatel
Keywords: urbanismus; bydlení; bytová politika; globalizace; city planning; housing; housing policy; globalization; elektronické knihy; studie; electronic books; studies